Statistical and graphic summary as of December 31, 1993 (Department of State San JuanPR, 1993)
Looks at the Caribbean Development Program; total job and investment promoted by Puerto Rico; and 936 financing in CBI countries. Provides a description of projects by country, projects listed by calendar year (1988-1993) and finally projects promoted by Puerto Rico's Bureau of Caribbean Basin Affairs as of Dec. 31, 1993.
DC